Halal Lifestyle: A Bibliometric Analysis - Maysyaroh, Siti; Akbar, Kelana Yudinta (SMART Insight, 2024)
Halal lifestyle is an approach to life that follows halal principles, as taught in Islamic teachings. The focus of this research is to try to find out the extent of the development of studies on the theme of Halal Lifestyle. The data analyzed consisted of 21 scopus indexed research publications. The data is then processed and analyzed using the VoS viewer application to find out the bibliometric map of research development related to Halal Lifestyle. Based on research using the bibliometric method found that there are at least 7 clusters of research maps related to Halal Lifestyle, namely: (1) Halal Lifestyle in Beauty Industries, (2) Halal Awareness, (3) Halal Lifestyle and Sharia Financial Literacy, (4) Halal Lifestyle on Product Development, (5) Halal Lifestyle and Sustainable Nutrition on Food, (6) Halal Lifestyle and Tolerant Society, and (7) Halal Lifestyle and Sharia Principle of Pool Management.